2020
DOI: 10.1111/ajae.12151
|View full text |Cite
|
Sign up to set email alerts
|

One Size Fits All? Experimental Evidence on the Digital Delivery of Personalized Extension Advice in Nigeria

Abstract: Blanket advice on optimal fertilizer application rates has failed to achieve potential yield gains for crop production in much of Sub‐Saharan Africa. However, digital technology now makes it possible to deliver personalized extension services to farmers at a much lower cost. We present results from a randomized control trial designed to evaluate the effectiveness of a mobile application that provides personalized advice on rice nutrient management. We find that households who were just given the personalized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 56 publications
2
55
0
Order By: Relevance
“…This result shows that the provision of more targeted extension farm advice is important, given the variations between the production systems. In agreement with this finding, Arouna et al [77] reported that farm households that received personalized advice increased their yield by 7% and profit by 10%, without increasing the quantity of production inputs, and hence by reducing inefficiencies.…”
Section: Discussionmentioning
confidence: 55%
“…This result shows that the provision of more targeted extension farm advice is important, given the variations between the production systems. In agreement with this finding, Arouna et al [77] reported that farm households that received personalized advice increased their yield by 7% and profit by 10%, without increasing the quantity of production inputs, and hence by reducing inefficiencies.…”
Section: Discussionmentioning
confidence: 55%
“…The hypothesis that attrition is not differentially determined by treatment status will be assessed through an F-test for the joint significance of the interaction terms in this regression. If differential determinants of attrition are observed, we will attempt to control for this through a weighting procedure as a robustness analysis [30]. Specifically, we will follow a two-stage procedure.…”
Section: Dealing With Attritionmentioning
confidence: 99%
“…This raises the need for research and development agents and policymakers to be able to identify the technology characteristics that drive the preferences of end users, who occupy a prominent node in the adoption decision process. Efforts to spur agricultural development have been met with continued low levels of adoption of improved technologies in SSA (Arouna et al 2020). Therefore, understanding the technology-specific characteristics that would motivate farmers to embrace improved technologies remains a high-priority research issue.…”
Section: Introductionmentioning
confidence: 99%